Age‐ and quality‐dependent DNA methylation correlate with melanin‐based coloration in a wild bird. Issue 13 (30th May 2018) - Soulsbury, Carl D.; Lipponen, Anssi; Wood, Kristie; Mein, Charles A.; Hoffman, Joseph I.; Lebigre, Christophe
Abstract: Secondary sexual trait expression can be influenced by fixed individual factors (such as genetic quality) as well as by dynamic factors (such as age and environmentally induced gene expression) that may be associated with variation in condition or quality. In particular, melanin‐based traits are known to relate to condition and there is a well‐characterized genetic pathway underpinning their expression. However, the mechanisms linking variable trait expression to genetic quality remain unclear. One plausible mechanism is that genetic quality could influence trait expression via differential methylation and differential gene expression. We therefore conducted a pilot study examining DNA methylation at a candidate gene (agouti‐related neuropeptide: AgRP ) in the black grouse Lyrurus tetrix . We specifically tested whether CpG methylation covaries with age and multilocus heterozygosity (a proxy of genetic quality) and from there whether the expression of a melanin‐based ornament (ultraviolet‐blue chroma) correlates with DNA methylation. Consistent with expectations, we found clear evidence for age‐ and heterozygosity‐specific patterns of DNA methylation, with two CpG sites showing the greatest DNA methylation in highly heterozygous males at their peak age of reproduction. Furthermore, DNA methylation at three CpG sites was significantly positively correlated with ultraviolet‐blue chroma. Ours is the first study to our knowledge to document age‐ and quality‐dependent variation in DNA methylation and to show that dynamic sexual trait expression across the lifespan of an organism is associated with patterns of DNA methylation. Although we cannot demonstrate causality, our work provides empirical support for a mechanism that could potentially link key individual factors to variation in sexual trait expression in a wild vertebrate. Abstract : We looked at how DNA methylation at CpG sites was related to both heterozygosity and blue coloration. We found a positive correlation between the percentage DNA methylation and blue coloration at prime reproductive age. We propose that DNA methylation is one potential means of translating condition dependence into sexual ornament expression.